Recent amendment to the Malaysian Family Law: A step to resolve interfaith custody disputes - Mohd Zin, Najibah; Abdul Hak, Nora; Hamid, Abdul Ghafur@Khin Maung Sein; Mohamed Jani, Hidayati (2017)
An interfaith custody dispute is one of the serious issues in Malaysia that have attracted a lot of concern not only from the legal practitioners but also the government, legal authorities, researchers and the public. Where one party to a non-Muslim marriage converts to Islam, the legality of the civil marriage would be affected, and more importantly it would give rise to a conflict in determining the custodial right of a child since the parties are now being subject to different set of laws and courts. Being a multiracial country, this issue needs to be resolved by the Malaysian government since it has created much confusion and dissatisfaction, particularly among non-Muslim communities and thus, it has become a matter of public interest. Consequently, an amendment to the Law Reform (Marriage and Divorce) Act 1976 was proposed and recently the amendment bill of the Law Reform (Marriage and Divorce)(Amendment) Act 2016 was tabled in the Malaysian Parliament. The aim of the amendment is to resolve interfaith custody conflicts between Muslim and non-Muslim parents. This paper seeks to examine the substance of the amendment bill particularly on the provisions, which relate to the issue of interfaith custody. The research method employed in this study is mainly a textual analysis of statutory provisions and case law relating to custody disputes involving interfaith parents. The result of the study suggests that the amendment seems not to resolve the conflict completely and other mechanisms or solutions are very much appreciated where the paramount consideration shall be the best interests of the child.